Security Challenges in Routing Protocols and a Proposed Schema in MANET - Kumar, Mayank; Muskan; Rohtash (International Journal of Computer Sciences and Engineering, 2014)
A Mobile Ad hoc network (MANET) is an intelligent automated dynamically distribution of wireless Mobile independent nodes they either connect straightforwardly or utilizing halfway node(s) without any predefined infrastructure. If there is no predefined infrastructure then networks get unprotected to number of attacks and elevated amount security turns into a real concern. The first section discusses brief introduction, features and routing protocols of MANET. The second section discusses the vulnerabilities in MANET. Mobile ad-hoc network (MANET) is one of the most necessary fields for study, development and research of wireless networks. Mobile Ad Hoc Networks (MANETs) has become one of the most frequent areas of research because of the security challenges it faces to its related protocols. The third section discusses the security challenges in routing protocols in MANET. The final section discusses Intrusion Detection Techniques (IDT), IDS architecture and conceptual model of IDS agent. MANET nodes are extensively changing & joining the mobile network. It is not possible to record the freed accomplished by node(s) in a dynamic network. Some of these nodes can become rogue and can become danger as these nodes belong to the trusted zone. This challenge is overcome by assigning a temporary id to each node. The paper proposes a novel algorithm to generate and assign a unique id for the nodes that are freed.